OLIGOPHRENIA - CLINICAL SIGNS OF MENTAL RETARDATION. (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
in today's article, mental retardation, Oligophrenia, i.e. mentally retarded children, is a collective concept, the time of occurrence of mental retardation, the character of the disease experienced, the course of pathological changes, and the level of the issues are covered.